Creativity and Cognitive Skills among Millennials: Thinking Too Much and Creating Too Little - Corgnet, Brice; Espín, Antonio M.; Hernán-González, Roberto (Frontiers in Psychology, 2016)
Organizations crucially need the creative talent of millennials but are reluctant to hire them because of their supposed lack of diligence. Recent studies have shown that hiring diligent millennials requires selecting those who score high on the Cognitive Reflection Test (CRT) and thus rely on effortful thinking rather than intuition. A central question is to assess whether the push for recruiting diligent millennials using criteria such as cognitive reflection can ultimately hamper the recruitment of creative workers. To answer this question, we study the relationship between millennials’ creativity and their performance on fluid intelligence (Raven) and cognitive reflection (CRT) tests. The good news for recruiters is that we report, in line with previous research, evidence of a positive relationship of fluid intelligence, and to a lesser extent cognitive reflection, with convergent creative thinking. In addition, we observe a positive effect of fluid intelligence on originality and elaboration measures of divergent creative thinking. The bad news for recruiters is the inverted U-shape relationship between cognitive reflection and fluency and flexibility measures of divergent creative thinking. This suggests that thinking too much may hinder important dimensions of creative thinking. Diligent and creative workers may thus be a rare find.